Bioinformatic Prediction of SNP Markers in WRKY Sequences of Palms - Manju, K. P.; Arunachalam, V. (International Coconut Community, 2011)
WRKY transcription factors are unique to plants and performs many imperative functions mainly disease resistance. In the present study we have analyzed the WRKY transcription factor gene sequences to assess the variation at single nucleotide level. We have retrieved 525 sequences of WRKY genes of palms of 334 Kb size. The sequences were purified by employing EST trimmer and were clustered into 31 contigs using CAP3. Single nucleotide Polymorphisms (SNP) and insertion/deletions (indels) were detected in contigs using the AUTOSNP software. Alternatively candidate SNP containing contigs were aligned by Clustal X to locate the SNPs. Results from these two methods were compared and false SNPs were eliminated. Finally, about 568 SNPs were found including 250 transitions, 120 transversions and 198 indels. The SNPs were seen at a frequency of 2.84/100bp in the WRKY sequences of palms. Primers were designed flanking to SNP/ indel sites with potential as markers in palms. We could obtain two novel WRKY-SNP markers (WRKY 7 and WRKY 12) which are not reported before in palms.